(x-3)(x-4)=34/(33*33)

Simple and best practice solution for (x-3)(x-4)=34/(33*33) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)(x-4)=34/(33*33) equation:


x in (-oo:+oo)

(x-3)*(x-4) = 34/(33*33) // - 34/(33*33)

(x-3)*(x-4)-(34/(33*33)) = 0

(x-3)*(x-4)-34/1089 = 0

(1089*(x-3)*(x-4))/1089-34/1089 = 0

1089*(x-3)*(x-4)-34 = 0

1089*x^2-7623*x+13034 = 0

1089*x^2-7623*x+13034 = 0

1089*x^2-7623*x+13034 = 0

DELTA = (-7623)^2-(4*1089*13034)

DELTA = 1334025

DELTA > 0

x = (1334025^(1/2)+7623)/(2*1089) or x = (7623-1334025^(1/2))/(2*1089)

x = 133/33 or x = 98/33

(x-98/33)*(x-133/33) = 0

((x-98/33)*(x-133/33))/1089 = 0

((x-98/33)*(x-133/33))/1089 = 0 // * 1089

(x-98/33)*(x-133/33) = 0

( x-133/33 )

x-133/33 = 0 // + 133/33

x = 133/33

( x-98/33 )

x-98/33 = 0 // + 98/33

x = 98/33

x in { 133/33, 98/33 }

See similar equations:

| 0.7x+6.52=-0.9x+2.12 | | 32x^2-5x-7=0 | | 170=(3x+5)(3x-2) | | 12(3x-3)=3(12x+4) | | 16+2=4+12 | | 9p+11=5p-5 | | 7f-6(f-3)=17 | | 1xy=-12 | | 7(k+4)-6k=28 | | 14=22-0.66x | | 4.4k=29.48 | | (-8y+1)-(-7y-6)=4 | | 7d*3e= | | -20x+20y=100 | | 8e-13=13 | | 8e-13=2 | | 5/x-1+4x/x+1=4 | | 12(3x+3)-5(2x-5)=6x-59 | | 7/5-9/2b= | | log(8)(7)+log(8)(11)=log(8) | | 5a-2(2+a)+3a= | | log(8)(7)+log(8)(11)= | | 2+b(4b)=22 | | -4(2n-7)= | | x^5+x^3+55=0 | | (x+5)(x+5)=-64 | | 2(y-6)+12=24 | | 10-4x+3=6x+5-7x | | -6k-k=45 | | X^2+xy^2+y^2=1 | | 6x^2-6x+10=2x^2+2x+25 | | h^2-8h+1=0 |

Equations solver categories